Faktor Faktor yang Mempengaruhi Psikologis Remaja di Masa Pandemi Covid-19 Kelas 7-8 di SMP Negeri 1 Naman Teran Tahun 2021 - Yuleen Natasya Telaumbanua; Lindawati Simorangkir; Imelda Derang (Journal of Indah Science and Clinic, 2022)
Psychology is part of the science of human psychology that can affect a person's life in his daily life. Factors that affect the psychology of adolescents during this pandemic are the implementation of social distancing, online learning, and theifearioficontractingiCOVID-19. Residents between the ages of 10 and 24 are considered adolescents. The study was to find out what are the factors that affect the psychology ofiadolescentsiduringitheiCovid-19ipandemiciin class VII and class VIII at SMP Negeri 1 Naman Teran ini2021. The research method usediwas a descriptiveiresearch designowithoaitotal ofo75 respondents. Theosamplingitechniqueousedowas purposiveosampling technique. The results showed that theomajorityoofistudentsodue toumild stress factors for the implementation of social distancing were 69 people (92.0%), the majority of students due to stress factors were online learning asimanyiasi58 peoplei(77.3%), anditheimajority of students due to fear of contracting covid. -19 with mild category as many as 64 people (85.3%). This shows that the factors of implementing social distancing, online learning and the feariofucontractingiCOVID-19iaffect the psychology of theistudents of SMP Negeri 1 Naman Teran. It is hoped that as information and material to increase their knowledge for students / I further increase their knowledge about the dangers of Covid-19 transmission.